Exile and Social Thought : Hungarian Intellectuals in Germany and Austria, 1919-1933. - Congdon, Lee (Princeton legacy library., 2014)
Embroiled in the political events surrounding World War I and the failed Hungarian revolutions of 1918-19, a number of intellectuals fled Hungary for Germany and Austria, where they essentially created Weimar culture. Among them were Georg Lukács, whose History and Class Consciousness recast Marxism and challenged even those who repudiated its politics; Bela Balázs, who pioneered film theory and collaborated with film-makers G.W. Pabst, Leni Riefenstahl, and Alexander Korda; László Moholy-Nagy, who codirected the Bauhaus during its heyday in the mid-1920s; and Karl Mannheim, whose Ideology.